The Veterans Specific Activity Questionnaire (VSAQ) - a new and efficient method of assessing exercise capacity in patients with pulmonary arteriovenous malformations - Gawecki,F; Myers,J; Shovlin,C (BMJ Open Respiratory Research, 2019)
INTRODUCTION: Assessment of performance status is an important component of clinical management of patients with pulmonary arteriovenous malformations (PAVMs). Usual methods are time-consuming and insensitive to variationswithinnormal or supranormal exercise capacity.METHODS: TheVeterans Specific Activity Questionnaire (VSAQ) wasmodifiedto facilitate completion by patients independently. Patient-reported activity limitations were converted to the MRC Dyspnea scale, NYHA Classification,and metabolic equivalents (METs) in which 1 MET equals the consumption of 3.5 ml O2per kilogram of body weight. RESULTS: The study population of71 patients with PAVMswas aged 20-85 (median 52) years.SaO2was80-99.5% (median 96%), and haemoglobin73-169g/L in females and 123-197g/L in males (p<0.0001). CaO2(1.34 x (haemoglobin ×SaO2)/100) was maintained unless iron deficiency was present. Most patients(49/71, 69%) did not need to stop until activities more energetic than walking briskly at 4 miles per hour were achieved (VSAQ >5; MRC Dyspnea Scale 1 or 2; NYHA Class I). SaO2was inversely associated with the MRC Dyspnea scale and NYHA class, but not theVSAQ. Raw VSAQ scores captured a marked difference between malesand females. METSwere also higherin malesat 3.97-15.55(median 8.84)kcal/kg/hour, compared to 1.33-14.4(median 8.25)kcal/kg/hour(p=0.0039). There was only a modest association between METsand oxygen saturation (SaO2, p=0.044), but a stronger association between METsand haemoglobin (p=0.001).In crude and sex-adjusted regression, the arterial oxygen content (CaO2) was more strongly associated with METsthan either SaO2or haemoglobin in isolation.CONCLUSION: The VSAQ,capturing patient reported outcome measures,is an efficient and quantifiable measure of exercise capacity that can be readily employed in clinical services particularly wherepatients have normal to high exercise tolerance. In th